2018
DOI: 10.1177/1470320318803009
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia activates the renin-angiotensin system and induces epithelial-mesenchymal transition in streptozotocin-induced diabetic kidneys

Abstract: Introduction:The renin–angiotensin system and epithelial–mesenchymal transition play crucial roles in the development of kidney fibrosis. The connection between the renin–angiotensin system and transforming growth factor-β in epithelial–mesenchymal transition remains largely unknown.Materials and methods:We assessed oxidative stress, cytokine levels, renal morphology, profibrotic growth factor and renin–angiotensin system component expression, and cell-specific E- and N-cadherin expression in the kidneys of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…In this study, we extensively investigated the mechanisms responsible for the therapeutic effects of JSD on DN, particularly focusing on liver and kidney dysfunction. Hyperglycemia induces renal injury through multiple pathways, including insulin resistance, glucose metabolism, hemodynamic disorders, inflammation, and fibrosis [29]. After long-term and chronic kidney damage in DN, incomplete tubular recovery leads to renal fibrosis and destroyed renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we extensively investigated the mechanisms responsible for the therapeutic effects of JSD on DN, particularly focusing on liver and kidney dysfunction. Hyperglycemia induces renal injury through multiple pathways, including insulin resistance, glucose metabolism, hemodynamic disorders, inflammation, and fibrosis [29]. After long-term and chronic kidney damage in DN, incomplete tubular recovery leads to renal fibrosis and destroyed renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ATR1 plays an important role in the pathogenesis of renal tissue injury. In an earlier study, it has been observed that hyperglycemia activates RAAS and contributes to renal fibrosis [15]. Ang II, the major mediator of kidney injury, displays majority of its deteriorating effects like generation of ROS, tissue inflammation, and fibrosis via activation of ATR1 [16].…”
mentioning
confidence: 99%
“…It is well-known that inhibitors of the reninangiotensin system delay the progression of diabetic kidney disease 32,33 . Furthermore, numerous studies have observed activation of the RAS in subjects with type 2 diabetes [34][35][36][37] . RAS and type 2 diabetes are closely related.…”
Section: Discussionmentioning
confidence: 99%